2022
DOI: 10.1002/mgg3.1880
|View full text |Cite
|
Sign up to set email alerts
|

Detection of germline mosaicism in fathers of children with intellectual disability syndromes caused by de novo variants

Abstract: Background De novo variants are a common cause to rare intellectual disability syndromes, associated with low recurrence risk. However, when such variants occur pre‐zygotically in parental germ cells, the recurrence risk might be higher. Still, the recurrence risk estimates are mainly based on empirical data and the prevalence of germline mosaicism is often unknown. Methods To establish the prevalence of mosaicism in parents of children with intellectual disability syndromes caused by de novo variants, we perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…While our methods theoretically allowed for finer detectability than in most similar studies, we did not identify a larger proportion of parental mosaics. The proportion of 3% is at the lower limit of previous studies on pathogenic DNV 7 . It is uncertain whether pathogenic variants of certain specific diseases could be associated with larger proportions of parental mosaics and what the underlying biological mechanism could be.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While our methods theoretically allowed for finer detectability than in most similar studies, we did not identify a larger proportion of parental mosaics. The proportion of 3% is at the lower limit of previous studies on pathogenic DNV 7 . It is uncertain whether pathogenic variants of certain specific diseases could be associated with larger proportions of parental mosaics and what the underlying biological mechanism could be.…”
Section: Discussionmentioning
confidence: 68%
“…Several studies aimed to assess the prevalence of parental mosaicism in presumed DNVs 7 . Some of them used large exome datasets of child-parents trios, obtained from blood samples, and with sequencing depths of coverage adapted to the detection of germline variants.…”
Section: Introductionmentioning
confidence: 99%
“…2). Furthermore, many cases of Kleefstra syndrome caused by nonsense, frameshift, and splice-site changes within this region have been reported [Willemsen et al, 2012;Bock et al, 2016;Huang et al, 2021;Frisk et al, 2022]. Additionally, Fear et al [2022] demonstrated that haplozygous cells of the truncated EHMT1 gene, a premature termination codon in the SET domain, confer features of Kleefstra syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish the prevalence of mosaicism in the parents of patients with intellectual disability syndromes caused by novel variants, Frisk et al ( 2022 ) performed ddPCR on DNA extracted from the blood of 43 trios and the sperm of 31 fathers. They detected low‐level mosaicism (EHMT1, c.2986C>T) only in the sperm‐derived DNA (1.1%) but not in blood.…”
Section: Discussionmentioning
confidence: 99%